Low-Temperature Melting and Glass Formation of the Zeolitic Imidazolate Frameworks ZIF-62 and ZIF-76 through Ionic Liquid Incorporation - Nozari, Vahid; Smirnova, Oksana; Tuffnell, Joshua M.; Knebel, Alexander; Bennett, Thomas D.; Wondraczek, Lothar (Advanced Materials Technologies, 2022)
Hybrid glass formation offers a potential route for processing metal-organic frameworks (MOFs) in bulk shapes, however, only a small number of MOFs have proven to be meltable. For the non-meltable zeolitic imidazolate framework ZIF-8, ionic liquid (IL) incorporation has recently been found to reduce the melting temperature to below the thermal decomposition temperature, thus, enabling the formation of IL@ZIF-8 glasses. Here, the effect of IL incorporation on the enthalpic response of some zeolitic imidazolate frameworks (ZIFs) and other MOFs upon heating is reported. For ZIF-62, ZIF-67, ZIF-76, and MIL-68, the accessibility of the metal site and MOF porosity govern the meltability of IL@MOF composites. IL incorporation enables the formation of ZIF-76 glasses, and significantly reduces the melting temperature of ZIF-62 but does not seem to facilitate the melting of ZIF-67 or MIL-68 (before thermal decomposition). Although the thermal stability limit of the IL plays an important role in governing the melting window of the IL@MOF composite, by careful selection of the melting temperature, thermal decomposition and compositional changes upon melting can be avoided to a greater extent. IL incorporation seems to offer a more universal route for melting MOFs, but requires careful adaption to the specific MOF architecture.
CRIS-Team Scopus Importer:2023-04-20
Keywords: hybrid glasses; ionic liquids; meltability; MOF glasses; zeolitic imidazolate frameworks